PENCEMARAN LINGKUNGAN LAUT AKIBAT LIMBAH PLASTIK DI PERAIRAN KEPULAUAN INDONESIA DITINJAU BERDASARKAN PENGATURAN HUKUM INTERNASIONAL DAN NASIONAL INDONESIA - Deayu Deayu; Suhaidi Suhaidi; Jelly Leviza (Journal of USU International Law, 2020)
ABSTRACT Prof.Dr. Suhaidi, SH.M.H* Dr. Jelly Leviza SH.M.Hum** Deayu*** Indonesia is an archipelago country where 70% of its territory is ocean. The crisis of the marine ecosystem due to plastic waste is currently very crucial and is being widely discussed. Plastic waste is bad for the environment because of the nature of the plastic that is difficult to decipher. The pattern of activities that are completely plastic can accelerate the process of reducing oxygen, increasing the killing of marine life, and damaging the digestive system of marine life and ultimately returning to our own losses. Further international legal provisions concerning the protection of the marine environment are regulated in the Stockholm Declaration 1972, London Convention 1972, London Protocol 1996, MARPOL 73/78, and UNCLOS 1982. National legal provisions in the prevention, reduction and management of marine environment pollution due to plastic waste can be seen in PP No.19 of 1999, Law No.32 of 2009. The role of the Indonesian state in the protection of the marine environment the scope of its implementation includes planning, controlling, maintaining, controlling, utilizing marine environment resources for the welfare of the people's lives and law enforcement such as Presidential Regulation No . 83 of 2018. The research method used in this study is a normative legal research method, where primary data is taken from international agreements and legislation that have relevance in this study. Based on the results of this study indicate that the quality of the environment including the declining marine environment will threaten the survival of human beings and other living things. Therefore, the international community through international organizations to further encourage countries to maintain the condition of the sea, as well as take all necessary measures to deal with the problem of pollution of the marine environment. Keywords: Archipelago Country, Marine Pollution, Plastic Waste